Comparative Study of Audiovestibular Symptoms between Early and Late Variants of COVID-19 - Ali A. Almishaal (Audiology Research, 2022)
Audiovestibular symptoms during the acute phase of the corona virus disease 2019 (COVID-19), have been reported for earlier waves of the pandemic, while no studies investigated nor compared audiovestibular manifestations during subsequent waves of COVID-19. In the current study, we aimed to compare the occurrence of audiovestibular symptoms associated with COVID-19 between the alpha/beta, delta, and omicron variants. An online questionnaire was distributed to individuals with confirmed test results for COVID-19. We asked participants to report whether they experienced audiovestibular symptoms during the acute phase of the disease. The study included 939 participants; 120 un-infected controls and infected participants during alpha/beta (n = 301), delta (n = 102), and omicron (n = 416) predominance periods. Self-reported audiovestibular symptoms were found to be statistically significantly different between un-infected controls and COVID-19 infected individuals in all analyzed variants. Furthermore, our results showed no significant differences in audiovestibular symptoms among individuals infected during alpha/beta, delta, and omicron waves. Although individuals infected during the delta variant predominance period reported higher percentages of audiovestibular symptoms (ranging from 11.8% to 26.5% for auditory symptoms and from 12.7% to 34.3% for vestibular symptoms) than for the alpha/beta (ranging from 6.3% to 18.9% for auditory symptoms and 8.3% to 29.9% for vestibular symptoms) and omicron (ranging from 9.6% to 21.2% for auditory and 12.5 to 29.1% for vestibular symptoms) variants, this did not achieve statistical significance. With regards to auditory symptoms, the most commonly reported symptoms were aural fullness followed by hearing loss and tinnitus. With regards to vestibular symptoms, dizziness was the most commonly reported symptom followed by vertigo and unsteadiness. Logistic regression revealed that experiencing auditory symptoms were associated with other neurological symptoms, back and joint pain, and chest pain as COVID-19 symptoms. Vestibular symptoms were associated with anemia, gender, fatigue, headache, and breathing difficulties. In conclusion, our study shows that audiovestibular symptoms are common during the acute phase of early and late COVID-19 variants with no significant differences between them.